2006
DOI: 10.1002/pds.1338
|View full text |Cite
|
Sign up to set email alerts
|

In‐hospital use of opioids increases rate of coded postoperative paralytic ileus

Abstract: This study demonstrated a distinct association between the use of opioids, in particular natural opium alkaloids, and the risk for coded POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Conversion of dispensed opioids to MED permits the quantification of morphine in all compounds. Morphine, unlike other opiates, has a more pronounced impact on POI 30 . It is a natural opium alkaloid with greater affinity and selectivity for mu-opioid receptors, and its metabolites are more potent than morphine itself.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Conversion of dispensed opioids to MED permits the quantification of morphine in all compounds. Morphine, unlike other opiates, has a more pronounced impact on POI 30 . It is a natural opium alkaloid with greater affinity and selectivity for mu-opioid receptors, and its metabolites are more potent than morphine itself.…”
Section: Discussionmentioning
confidence: 94%
“…Intravenously administered morphine has a more pronounced effect on the mu-opioid receptors in the gut than epidural administration 30 . Barletta et al in their study of 279 patients undergoing open and laparoscopic colectomies found a correlation of intravenous opioid use with total hydromorphone dose, maximum daily hydromorphone dose, average daily hydromorphone dose and days of intravenous narcotics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,29,30 In the setting of postsurgical analgesia, opioids are frequently administered via patientcontrolled analgesia (PCA) devices that permit selfadministration of small opioid doses which allow patients to have some control of the prescribed analgesic regimen. 1,31 Although the use of PCA improves pain control and patient satisfaction, 32 the incidence of ADEs associated with opioid PCA appears similar to that associated with other methods of administration.…”
Section: The Challenge Of Ades and The Rationale For Multimodal Analgmentioning
confidence: 99%